Optimizing Bioplastic Production of C. necator Under Mixotrophic Fermentation with CO2 and Glucose - Unaha, Dueanchai; Jaihao, Pongpipat; Unrean, Pornkamol; Champreda, Verawat (Waste and biomass valorization, 2024)
Purpose Herein, we examined C. necator for its production of bioplastic under mixotrophic fermentation. The mixotrophic process utilized dual carbon sources of mixed CO 2 and glucose for the production of PHB. Methods C. necator was optimized through adaptive laboratory evolution under a mixed carbon sources of CO 2 and glucose. The isolated mutant was then studied for its ability to co-utilize glucose and CO 2 carbon sources for growth and for PHB production. Experimental design based on central composition design was implemented to optimize PHB production under mixotrophic fermentation. Parameters effecting PHB accumulation including CO 2 and glucose substrate ratio, cell dosage and aeration were studied. Results Under optimized mixotrophic batch process, 0.22 g/L of PHB and 28% PHB content was reached from mixed carbon sources. Further CO 2 and glucose co-feeding strategy optimization in mixotrophic fed-batch, PHB titer was elevated to 0.41 g/L. Conclusion Overall, this study offered a promising alternative for CO 2 valorization through the mixotrophic conversion of CO 2 and glucose to PHB by C. necator , which could provide basis in future Bio-CCU technology development for climate change mitigation. Graphical Abstract